Quadrotor simulation, configuration, calibration, tuning and wireless communication - Ewan, Alexander Moyes. (2013)
The interest in UAV technology is increasing in engineering and military usage and now even hobbyists are experimenting with UAV designs. This specialized area is becoming increasingly accessible as research in the area is being rapidly and globally developed. This thesis looks at the complex dynamics of the quadrotor UAV which the control board is responsible for and analyses the dynamics using Newton’s equations of motion and quaternion method for representing Euler’s angles. The controller can then autonomously control the quadrotor using the system dynamic equations. A MatLab Simulink model has been created to highlight the importance of a controller and disturbance testing is carried out on a hovering quadrotor model. The main steps carried out to assembling the quadrotor are described in this document including images of the final product created.